ANALYSIS OF THE ROMANIAN ADVERTISING MARKET - CHIRILA SOFIA; ABONTU CECILIA IRINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2010)
Once with the gradual disappearance of the monopoly of the state and the socialist economy, the Romanians were forced to reinvent advertising and marketing communications. The tests on our own have turned into a need to professionalize these fields, which are one of the most powerful engines of the economy and contemporary social life. Reinventing turned, as so often in our modern history, into a synchronization process, of rapid combusting stage;the talent and the enthusiasm of the Romanian advertisers were molded on the prescriptions and the institutions that already had a stock of knowledge accumulated during more than a century. The result was a continuous progress, resulted in a spectacular economic growth of the industry and in the awards obtained by local creations at international festivals. The TV spots, radio, posters, giant billboards and press designs have become some of the most spectacular manifestations of contemporary culture, they are brilliant, eyecatching, arouse strong emotions and desires, require that we identify with the characters that we love, make us smile or make us think.